PAG1, a cotton brassinosteroid catabolism gene, modulates fiber elongation. Issue 2 (2nd May 2014) - Yang, Zuoren; Zhang, Chaojun; Yang, Xiaojie; Liu, Kun; Wu, Zhixia; Zhang, Xueyan; Zheng, Wu; Xun, Qingqing; Liu, Chuanliang; Lu, Lili; Yang, Zhaoen; Qian, Yuyuan; et al.
Summary: Cotton ( Gossypium hirsutum ) is the major source of natural textile fibers. Brassinosteroids (BRs) play crucial roles in regulating fiber development. The molecular mechanisms of BRs in regulating fiber elongation, however, are poorly understood. pagoda1 (pag1) was identified via an activation tagging genetic screen and characterized by genome walking and brassinolide (BL) supplementation. RNA‐Seq analysis was employed to elucidate the mechanisms of PAG1 in regulating fiber development. pag1 exhibited dwarfism and reduced fiber length due to significant inhibition of cell elongation and expansion. BL treatment rescued its growth and fiber elongation. PAG1 encodes a homolog of Arabidopsis CYP734A1 that inactivates BRs via C‐26 hydroxylation. RNA‐Seq analyses showed that the constitutive expression of PAG1 downregulated the expression of genes involved in very‐long‐chain fatty acids (VLCFA) biosynthesis, ethylene‐mediated signaling, response to cadmium, cell wall development, cytoskeleton organization and cell growth. Our results demonstrate that PAG1 plays crucial roles in regulating fiber development via controlling the level of endogenous bioactive BRs, which may affect ethylene signaling cascade by mediating VLCFA. Therefore, BR may be a critical regulator of fiber elongation, a role which may in turn be linked to effects on VLCFA biosynthesis, ethylene and cadmium signaling, cell wall‐ and cytoskeleton‐related gene expression.